2017
DOI: 10.2519/jospt.2017.7348
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Response Following a Thoracic Spinal Manipulation in Healthy Men

Abstract: Study Design Controlled laboratory study. Background Spinal manipulation (SM) can trigger a cascade of responses involving multiple systems, including the sympathetic nervous system and the endocrine system, specifically, the hypothalamic-pituitary axis. However, no manual therapy study has investigated the neuroendocrine response to SM (ie, sympathetic nervous system-hypothalamic-pituitary axis) in the same trial. Objective To determine short-term changes in sympathetic nervous system activity, heart rate var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 79 publications
2
36
0
5
Order By: Relevance
“…1). Of these, 16 deal with mobilizations (oscillatory technique) [35–50], 1 with an atypical mobilization technique [51], 5 with sustained natural apophyseal glides (SNAGs) / mobilization with movement [5256], and 7 with high velocity low amplitude manipulation [5763]. The experimental interventions were undertaken in various parts of the spine but also in the extremities in two studies [38, 52] and the effects were reported in relation to skin conductance ( N = 15), heart rate ( N = 11), skin temperature ( N = 11), blood pressure ( N = 7), HRV ( N = 5), respiratory rate ( N = 3), skin blood flow ( N = 3), biochemical markers ( N = 2), pupil diameter ( N = 1), and oxy-hemoglobin concentration ( N = 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Of these, 16 deal with mobilizations (oscillatory technique) [35–50], 1 with an atypical mobilization technique [51], 5 with sustained natural apophyseal glides (SNAGs) / mobilization with movement [5256], and 7 with high velocity low amplitude manipulation [5763]. The experimental interventions were undertaken in various parts of the spine but also in the extremities in two studies [38, 52] and the effects were reported in relation to skin conductance ( N = 15), heart rate ( N = 11), skin temperature ( N = 11), blood pressure ( N = 7), HRV ( N = 5), respiratory rate ( N = 3), skin blood flow ( N = 3), biochemical markers ( N = 2), pupil diameter ( N = 1), and oxy-hemoglobin concentration ( N = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Low-certainty evidence (Table 3 P, Q) suggests that spinal manipulation may have no acute effect on cardiac autonomic activity, as there was no effect on various HRV components immediately after the intervention. There was no effect on the spectral power of the normalized HF component (mean difference 1.16, 95% CI -4.86 to 7.18, I 2 = 0%, p = 0.71, 3 studies [5759]), no effect on the spectral power of the normalized LF component (mean difference 2.84, 95% CI -3.47 to 9.14, I 2 = 0%, p = 0.38, 3 studies [5759]), and no effect on the LF / HF ratio (mean Difference − 0.06, 95% CI -0.34 to 0.22, I 2 = 0%, p = 0.67, 4 studies [5759, 63]). Sampath et al [63] also reported no effect on the LF / HF ratio 30 min after the intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…not during the very immediate period after the interventions), since we first measured the sensitivity to experimentally induced pain. This is different from the sham-controlled trials included in the previous review which measured HRV within the 5 min [34,[50][51][52] after the interventions. Our results at short term (i.e.…”
Section: Comparison With Previous Literaturementioning
confidence: 71%
“…Our results at short term (i.e. 30-40 min) are also in accordance with another sham-controlled trial that reported no RRi intervals between normal beats; Log logarithm with base 10; HF high frequency; HF normalized unit: HF/(HF + LF) x 100; LF low frequency; RMSSD root mean square of the successive differences between normal heartbeats; SDNN standard deviation of the inter beat interval of normal sinus beats; SBP systolic blood pressure; DBP diastolic blood pressure; MBP mean blood pressure effect on the LF/HF ratio 30 min after the intervention [52]. However, a recent sham-controlled trial [21] reported a statistically significant effect of a thoracic HVLA manipulation on a time domain index of HRV (increase of RMSSD) within the 60 s following the intervention.…”
Section: Comparison With Previous Literaturementioning
confidence: 99%